"As if I Really Mattered": The Narrator of Sinclair Ross’s As For Me and My House - Compton, Anne (Studies in Canadian Literature, 1992)
Most critics of Sinclair Ross’s As For Me and My House give more critical attention to the narrated character, Philip, but the novel is Mrs. Bentley’s journal; she is the maker of the story. Ross offers the reader an unusual experience: a male-authored text in which the reader is invited to identify with a feminine experience and perspective presented as the human one. Mrs. Bentley is both powerless – oppressed in the spatial, temporal, physical, and marital spheres – and a manipulator, whose attempts to bind her husband to her alienate some readers. In her diary, Mrs. Bentley struggles against her worst fear: her own unimportance. She articulates for readers the yearning that our lives mean something. Ross creates a tough-minded, ruthlessly frank, female narrator, one whose words name, and in the naming overcome, the conditions that threaten her.